Faktor-faktor yang mempengaruhi Implementasi Computer Assisted Audit Techniques: Performance Expectations, Effort Expectations dan Social Influence - Hendi, Hendi Ependi; Kuntadi, Cris (Jurnal Manajemen, Akuntansi dan Logistik (JUMATI), 2024)
The implementation of Computer Assisted Audit Techniques (CAATs) has become an important strategy in improving the effectiveness and efficiency of the audit process, especially in facing an increasingly digital business environment. This study aims to analyze the factors that influence the implementation of CAATs in auditors, focusing on performance expectations, effort expectations, and social influence as the main variables. This study uses a quantitative approach with a survey method on auditors working in various industrial sectors. Data were collected through questionnaires filled out by respondents and analyzed using multiple regression techniques to test the effect of each variable on the implementation of CAATs. The results showed that performance expectations and social influence had a significant positive effect on the implementation of CAATs. Auditors who have high expectations for improving performance with CAATs and feel strong social support from colleagues or management are more likely to adopt CAATs in their work. Conversely, effort expectations showed an insignificant effect, indicating that perceptions of the effort required to use CAATs do not substantially affect adoption decisions. This study contributes to audit practitioners and policy makers to better understand the factors that support the adoption of audit technology. The practical implication of these findings is the importance of increasing performance awareness and social support to encourage wider implementation of CAATs.